Analisis Tingkat Efisiensi Bank Umum Syariah yang Listing di Bursa Efek Indonesia Tahun 2019-2022 (Studi Deskriptif) - Hafiz Naufal Hilmi; Ima Amaliah (Bandung Conference Series: Economics Studies, 2023)
Abstract. Islamic Commercial Banks (BUS) have grown rapidly in recent years, attracting the interest of various groups. Analyzing the performance of BUSs listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022 is very interesting because this sector has many opportunities and challenges, including those caused by the covid-19 pandemic, regulatory changes, and increased competition in the banking industry. Based on this phenomenon, the problems in this study are formulated as follows: (1) What is the efficiency level of BUSs listed on the IDX in using their inputs on 2019 to 2022? (2) What is the efficiency level of BUSs listed on the IDX in producing outputs on 2019 to 2022? (3) What is the overall performance efficiency level of BUSs listed on the IDX on 2019 to 2022? This research will use a descriptive study approach using secondary data. The population used is four BUSs listed on the IDX, Aladin Syariah, BSI, BTPN Syariah and Panin Dubai Syariah with inputs of DPK, total labor, operational costs and capital. While the output is Financing, CAR, BOPO and NI. The results of this study Based on descriptive studies, BUSs listed on the IDX show efficiency in managing their inputs, with BSI being the most efficient. Meanwhile, seen from the output, BTPN Syariah, BSI, and Panin Dubai Syariah managed to achieve efficiency. with BTPN Syariah being the most efficient in managing its output. Overall, BTPN Syariah showed the most efficient performance among the BUSs listed on the IDX. Abstrak.Bank Umum Syariah (BUS) telah berkembang pesat dalam beberapa tahun terakhir, menarik minat berbagai kalangan. Analisis kinerja BUS yang terdaftar di Bursa Efek Indonesia (BEI) dari tahun 2019 hingga 2022 menjadi sangat menarik karena sektor ini memiliki banyak peluang dan tantangan, termasuk yang disebabkan oleh pandemi covid-19, perubahan peraturan, dan meningkatnya persaingan di industri perbankan. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) a. Bagaimana tingkat efisiensi BUS yang listing di BEI dalam penggunaan inputnya selama periode 2019 hingga 2022? (2) Bagaimana tingkat efisiensi BUS yang listing di BEI dalam menghasilkan output selama periode 2019 hingga 2022? (3) Bagaimana tingkat efisiensi kinerja keseluruhan BUS yang listing di BEI selama periode 2019 hingga 2022? Penelitian ini akan menggunakan pendekatan studi deskriptif dengan menggunakan data sekunder. Populasi yang digunakan adalah empat BUS yang listing di BEI, Aladin Syariah, BSI, BTPN Syariah dan Panin Dubai Syariah dengan input DPK, jumlah tenaga kerja, biaya operasional dan modal. Sedangkan outputnya adalah Pembiayaan, CAR, BOPO dan NI. Hasil penelitian ini Berdasarkan studi deskriptif, BUS-BUS yang terdaftar di BEI menunjukkan efisiensi dalam mengelola inputnya, dengan Bank BSI menjadi yang paling efisien. Sedangkan, dilihat dari outputnya, BTPN Syariah, BSI, dan Panin Dubai Syariah berhasil mencapai efisiensi. dengan BTPN Syariah menjadi yang paling efisien dalam mengelola outputnya. Secara keseluruhan, BTPN Syariah menunjukkan kinerja paling efisien di antara BUS-BUS yang terdaftar di BEI.Abstract. Islamic Commercial Banks (BUS) have grown rapidly in recent years, attracting the interest of various groups. Analyzing the performance of BUSs listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022 is very interesting because this sector has many opportunities and challenges, including those caused by the covid-19 pandemic, regulatory changes, and increased competition in the banking industry. Based on this phenomenon, the problems in this study are formulated as follows: (1) What is the efficiency level of BUSs listed on the IDX in using their inputs on 2019 to 2022? (2) What is the efficiency level of BUSs listed on the IDX in producing outputs on 2019 to 2022? (3) What is the overall performance efficiency level of BUSs listed on the IDX on 2019 to 2022? This research will use a descriptive study approach using secondary data. The population used is four BUSs listed on the IDX, Aladin Syariah, BSI, BTPN Syariah and Panin Dubai Syariah with inputs of DPK, total labor, operational costs and capital. While the output is Financing, CAR, BOPO and NI. The results of this study Based on descriptive studies, BUSs listed on the IDX show efficiency in managing their inputs, with BSI being the most efficient. Meanwhile, seen from the output, BTPN Syariah, BSI, and Panin Dubai Syariah managed to achieve efficiency. with BTPN Syariah being the most efficient in managing its output. Overall, BTPN Syariah showed the most efficient performance among the BUSs listed on the IDX.